To Infinity and Beyond-The Impact of Knowledge Upload on People and Society - Fisher, Eddie John Paul; Fisher, Eddie (Business and Economic Research, 2024)
The continuously improving advances in artificial intelligence (AI) technology have been the driving force behind innovative approaches to develop the field of direct knowledge upload between human brains. The results from this research confirm that there is a widening gap between knowledge transfer solutions and associated ethical and social concerns. Implications to the individual and society include technological abuse, data privacy, human intellect intellectual property (IP), prejudice and discrimination. Associated costs suggest that knowledge upload can make the benefits of it upload exclusively available to affluent people. The primary focus of scientists and researchers must place more emphasis on knowledge transfer solutions that are in the best interests of people and society. The current widening collaboration and partnership gaps between developers and scientists must be closed through the sharing of relevant knowledge and insights, setting aside cultural and geographical differences. New legislation is needed to protect people and society in ethics and social concerns. Knowledge upload reversal requires further investigation to prove its impacts/side-effects and to generate acceptable proven solutions to resolve these.